An Analysis of Consumer Awareness About Consumer Protection Act in the State of Goa - Case Study Analysis - Silva, Priyanka Da (International Journal of Psychosocial Rehabilitation, 2020)
Consumer is to be protected from unsafe products, poor quality of goods and services, high prices, unfair trade practices and misleading advertisements. The present study on “An Analysis of Consumer Awareness about Consumer Protection Act in the State of Goa- Case Study Analysis” aims to study the level of Consumer awareness regarding Consumer Protection Act and to study the factors involved in increasing the level of Consumer Awareness about Consumer Protection. For the purpose of study, 150 respondents were selected randomly from South Goa and were interviewed. From the study it was found that most of the respondents are aware about the Act and their rights. Factor Analysis has reduced the dimension of the 14 factors into 4 major components. They are, promotion measures, providing relevant information, bringing mutual understanding and knowledge regarding solution of problems.